Acute Fifth Metatarsal Tuberosity Fractures: A Systematic Review of Nonoperative Treatment. Issue 4 (25th August 2020) - Khan, Shawn; Axelrod, Daniel; Paul, Ryan; Catapano, Michael; Stephen, David; Henry, Patrick; Wasserstein, David
Abstract : Objective: Acute metatarsal fractures are a common lower extremity injury. Although surgery may be recommended in specific cases, most are treated nonoperatively. Treatment protocols vary significantly among practitioners, with no consensus on the most efficacious approach. This systematic review aims to identify the effect of treatment protocols on union rate and functional outcome after an acute fifth metatarsal tuberosity fracture. Literature Survey: Multiple databases, including CINAHL, EMBASE, MEDLINE, and the Cochrane CEntral Register of Controlled Trials (CENTRAL) were searched from database inception to March 4, 2018 to identify clinical studies addressing nonoperative management of metatarsal fractures reporting nonunion, pain, and/or length of recovery. Methodology: Two reviewers independently completed title, abstract, and full‐text screening. Data abstraction was completed in duplicate. Outcome measures and complications were descriptively analyzed. Synthesis: A total of 1941 studies were eligible for screening. Seven studies (four randomized controlled trials and three prospective cohort studies) satisfied inclusion criteria. This resulted in a total of 388 patient with acute fifth metatarsal tuberosity fractures in 12 different treatment arms, with the most common treatment including plaster casting (7). The mean age was 42 years (27 to 56 years), and the overall nonunion rate was low (1.1%). Four unique functional scores were reported across all studies, and all showed good to excellent short‐term results. The overall qualities of studies were moderate, with particular limitations in randomization and concealment allocation. Conclusion: Most acute fifth metatarsal tuberosity fractures heal well, with good‐to‐excellent functional outcomes with nonoperative treatment, regardless of technique. We recommend a conservative rehabilitation framework, including 2 to 3 weeks of immobilization in a walking cast, followed by gradual increase in activity and strengthening until clinical union is achieved.